Popular Culture in Asia - Fitzsimmons, Lorna. author. aut Link
IX, 222 p.
Keywords: Popular Culture in Asia consists studies of film, music, architecture, television, and computer-mediated communication in China, Japan, South Korea, Taiwan, the Philippines, Malaysia, and Singapore, addressing three topics: urban modernities; modernity, celebrity, and fan culture; and memory and modernity.